2014
DOI: 10.1590/s0100-736x2014000300011
|View full text |Cite
|
Sign up to set email alerts
|

Características histomorfológicas e histoquímicas determinantes no diagnóstico da criptococose em animais de companhia

Abstract: Pesq. Vet. Bras. 34(3):261-269, março 2014 261 RESUMO.-Sete casos de criptococose (seis gatos e um cão) foram estudados para estabelecer as características histomorfológicas e histoquímicas determinantes no diagnóstico histopatológico dessa condição. Os dados complementares relacionados à epidemiologia, aos aspectos clínicos, à localização das lesões e às alterações macroscópicas foram obtidos dos protocolos de necropsias e biópsias. Na histologia, as leveduras foram observadas no interior de macrófagos o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 33 publications
(59 reference statements)
2
4
0
16
Order By: Relevance
“…The clinical signs presented by the goat, as well as the gross and histological findings observed in the lungs, are similar to those described by other authors in domestic animals (GUTIÉRREZ & MARÍN, 1999;KOMMERS et al, 2005;LEMOS et al, 2007;LUVIZOTTO et al, 2009;GALIZA et al, 2014). In goats, the lungs appeared to be the major organs affected by cryptococcosis (BARÓ et al, 1998), and the lesions observed in this goat explain the dyspnea, cough and nasal discharge.…”
supporting
confidence: 87%
“…The clinical signs presented by the goat, as well as the gross and histological findings observed in the lungs, are similar to those described by other authors in domestic animals (GUTIÉRREZ & MARÍN, 1999;KOMMERS et al, 2005;LEMOS et al, 2007;LUVIZOTTO et al, 2009;GALIZA et al, 2014). In goats, the lungs appeared to be the major organs affected by cryptococcosis (BARÓ et al, 1998), and the lesions observed in this goat explain the dyspnea, cough and nasal discharge.…”
supporting
confidence: 87%
“…Among the fungi that can cause pneumonia, cryptococcosis has the largest number of cases reported in Brazil; however, case reports describe patients mainly with neurological signs (Marcasso et al 2005, Martins et al 2008, Campos et al 2009, Galiza et al 2014, Headley et al 2016, one dog with cutaneous infestation (Martins et al 2014) and another with nasal infection (Pereira et al 2013). Dog A in this study, besides cough with no response to antibiotic treatment, had other clinical signs compatible with a mycotic disease, including fever, lymphadenopathy, and hyphema (Ferreira et al 2007, Greene & Bromel 2012, Hawkins 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Esta técnica já tinha sido utilizada na detecção da cápsula de polissacarídeos e da parede celular de Cryptococcus spp. em outro estudo (Galiza et al 2014).…”
Section: Discussionunclassified
“…se mostram fortemente positivos nesta coloração (Kwon-Chung et al 1981, Galiza et al 2014. As diferenças marcantes entre Sporothrix spp.…”
Section: Discussionunclassified
See 1 more Smart Citation